A Community Evaluation Of Action Plan (CAP) In Slum Settlement Arrangement In Villageskedaung Kaliangke West Jakarta - Riya Irawati; Mustika Berliantoro; Imam Mujahid A; Neneng Sri Rahayu (Journal of Public Administration and Government, 2023)
According to the Spatial and Regional Plan of DKI Jakarta Province, Kedaung Kaliangke Subdistrict is one of the targeted areas for urban redevelopment through a slum area revitalization program. The Community Action Plan (CAP) program in Kedaung Kaliangke Subdistrict began implementation at the end of 2018 and served as a pilot project area for this program, alongside several other subdistricts in the West Jakarta Administrative City region. This research aims to evaluate the CAP program using Stake's Analysis, followed by the formulation of conclusions and recommendations for improving the implementation of CAP in addressing slum settlements in Kedaung Kaliangke Subdistrict. The research findings, based on Stake's analysis of readiness, processes, and outcomes, indicate that the CAP program in Kedaung Kaliangke Subdistrict has not been optimal and effective in improving the quality of housing. There is also a lack of collaboration from sectors outside the housing and settlement department, leading to neglect in maintaining and caring for infrastructure through the CAP and CIP programs. Recommendations for improvement include the need for community awareness campaigns about the CAP program before activities commence, enforcing transparency in the administrative process, extending the duration of CAP implementation, and selecting priority programs tailored to the community's needs as a solution to address the issues faced by the population.